2004
DOI: 10.1152/japplphysiol.01106.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-induced vasoconstriction of the carotid artery, a possible causative factor of heatstroke

Abstract: Clinical and experimental studies indicate that hyperthermia can cause heatstroke with cerebral ischemia and brain damage. However, no study has examined the direct effects of heating carotid artery smooth muscle and tested the hypothesis that hyperthermia induces arterial vasoconstriction and, thereby, decreases cerebral blood flow. We recorded isometric tension of rabbit carotid artery strips in organ baths during stepwise temperature elevation. The heating responses were tested at basal tone, in norepinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
(18 reference statements)
4
21
1
Order By: Relevance
“…Similar results were found with in vivo hyperthermia in dogs, where at a core temperature of 408C systemic vascular resistance significantly decreased [19]. Other studies on the arteries of various animals have shown that hyperthermia induced vasoconstriction [9,11,20]. It was postulated that this heating-induced contraction was mediated by the inhibition of K þ channels [20].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were found with in vivo hyperthermia in dogs, where at a core temperature of 408C systemic vascular resistance significantly decreased [19]. Other studies on the arteries of various animals have shown that hyperthermia induced vasoconstriction [9,11,20]. It was postulated that this heating-induced contraction was mediated by the inhibition of K þ channels [20].…”
Section: Introductionsupporting
confidence: 79%
“…Other studies on the arteries of various animals have shown that hyperthermia induced vasoconstriction [9,11,20]. It was postulated that this heating-induced contraction was mediated by the inhibition of K þ channels [20]. The same study showed a decrease in contractility at high temperatures in response to norepinephrine and electrical field stimulation (EFS).…”
Section: Introductionmentioning
confidence: 94%
“…Lastly, reductions in CBF during heat stress may also be influenced by direct influences of temperature on the vascular smooth muscle cells. For example, heating isolated carotid artery rings of the rabbit induce temperature-dependent vasoconstriction, explained by the inhibition of potassium channels (316). It remains unknown if similar vasogenic consequences of temperature itself are present in the intact vessel.…”
Section: Arterial Blood Gasesmentioning
confidence: 99%
“…This stimulus may also decrease the resistance of upstream feed arteries (1). Although in some ex vivo experiments heating relaxes isolated blood vessels, especially cutaneous veins (2), it is evident that in the majority of animal studies heating per se does not change or slightly increases the tone of (arterial) blood vessels, such as in mesenteric and carotid arteries (19,22). These latter observations are in line with the understanding that warm blood is shunted from the body's core to skin so that heat can more effectively be released, although clearly sympathetically mediated vasoconstriction is the primary driver of this response.…”
mentioning
confidence: 99%